Keutuhan Rumah Tangga Yang Harmonis Dan Sejahtera Implemetasi UU No. 23 Tahun 2004: Penelitian - Mohamad Mundir; Indra Yuliawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The family is a fundamental social unit that plays a vital role in shaping individual well-being in physical, mental, emotional, and social aspects. Family harmony serves as the foundation for developing a healthy personality and a prosperous society. However, in reality, conflicts, violence, and injustice often threaten household integrity. This article aims to analyze the concept of a harmonious and prosperous family from a legal perspective, particularly through the implementation of Law No. 23 of 2004 on the Elimination of Domestic Violence (UU PKDRT). The study applies a normative legal research method with a descriptive qualitative approach based on a literature review, covering primary, secondary, and tertiary legal materials. The findings indicate that a harmonious and prosperous family cannot rely solely on religious teachings and moral values but also requires firm legal instruments to protect family members, especially women and children, from threats of physical, psychological, sexual violence, and neglect. Therefore, synergy among religious values, social norms, and positive law is essential to achieve a harmonious, peaceful, and prosperous household in line with national ideals.